KOMODIFIKASI FANDOM BLACKPINK DI INDONESIA - Tuty Mutiah, Mutiah; Adityo Fajar; Ilham Albar Pane; Chepi Nurdiansyah; A Rafiq (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2023)
Fandom is a term used to describe activities that reflect the closeness between fans and their idols based on a particular cultural product. Advances in digital technology have made interaction between fandoms and their idols easier, enabling them to consume a variety of products issued by such idols. Unfortunately, fandom activity on digital media is often exploited in the form of collecting user data that is then exploited for commercial purposes. Sometimes, digital media consumption can even become a "job" that users do not realize, which ultimately benefits content providers and platforms. This research aims to explore how fandom exploitation happens in a Blackpink fandom case study in Indonesia. In data analysis, concepts such as "playbour" (the work done by fans in support of their idols), "datafication" (transforming activity into data), and "commodification" (converting something into commodity) are used as a framework. The process of fandom exploitation begins with an attempt to build emotional closeness between idols and fans. Idola is present in a variety of content, both music-related and non-musical. fandom data is obtained through various activities of digital media consumption and the formation of dedicated membership within the community. By leveraging the enthusiasm of the fans, capital owners and associates take further steps to maximize their profits. They can collaborate with a variety of brands that may not have a direct connection to music, but rely on idol popularity to boost their sales or brand image.